Persepsi Siswa Tentang Keterampilan Dasar Mengajar Guru Matematika Pasca Pandemi Covid-19 - Rizaldi Muharman Syah; M Imamuddin (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
This research is a survey research. The survey was conducted at MAN 4 Religion. The number of samples is 49 students taken by proposive sampling. Data on students' perceptions of teachers' teaching skills were obtained from distributing questionnaires to students. The results of the questionnaire were analyzed descriptively using the percentage formula. the results of this study are as follows; students' perceptions of the teacher's opening and closing skills, the highest rating when the teacher gives motivation to students is 58%, the highest explanation skills are obtained when the teacher places emphasis on 45%, on questioning skills the highest rating when the teacher encourages students to ask 42%. for the skills to provide the greatest variety of assessments is to provide variations in activities with an achievement of 43%, for the skills to provide reinforcement by the teacher the highest score is 41% namely on strengthening with expressions, reprimanding students wisely obtaining 34% on classroom management skills, and on guiding skills The highest student response group discussion was given to providing the opportunity to participate, namely by 43%.